ПОВЫШЕНИЕ КАЧЕСТВА ЖИЗНИ ПОЖИЛЫХ ЛЮДЕЙ ПУТЕМ ПРОЛОНГИРОВАНИЯ АКТИВНОГО ОБРАЗА ЖИЗНИ - Н. В. Агранович; В. О. Агранович; М. С. Кульнева (SINAPS LLC, 2012)
Clinical geriatric practice, you must exclude the idea of old age as a disease. An active lifestyle in later age depends on many factors, understanding that successful implementation of policies and programs aimed at creating an integrated model. Relevant in this regard is the need to analyze the basic medical and social factors, narrowing the possibility of extending the active lifestyles of elderly people. Each of the stages of medical and social assistance to the elderly and senile age has its own characteristics to be taken into account in the further improvement of this category of persons. And only their harmonious combination will improve quality and save the active life position for many years.